Arctic Fox (Alopex lagopus) Diet in Karupelv Valley, East Greenland, during a Summer with Low Lemming Density - Dalerum, Fredrik; Angerbjörn, Anders (ARCTIC, 2000)
We investigated the diet of arctic foxes (Alopex lagopus) in the Karupelv valley, East Greenland, during the summer of 1997. Despite a low density, lemmings were the most utilized prey, comprising 65.3% of dry fecal weight in fresh feces. This demonstrates the importance of lemming species as prey for arctic foxes all through a lemming cycle. Birds, arctic hare (Lepus arcticus), and insects also contributed to the diet. Arctic fox remains suggested that the foxes had scavenged their own species. Vegetation, muskoxen (Ovibos moschatus), and seal (Phocidae) were found in small amounts. We compared estimates of prey availability and diets of arctic foxes for a coastal area (<10 km from the shore) and an inland area (>10 km from the shore). Abundance of avian prey tended to be higher in the coastal area. Fresh feces indicated a significant overall difference in arctic fox diets between the coastal and inland areas. Within prey categories, lemmings were significantly more represented in the inland area, while the coastal area had a more diverse diet overall. We also suggest that the existence of arctic foxes in East Greenland is dependent on regular peak years in lemming density. Au cours de l'été de 1997, on a étudié le régime alimentaire du renard arctique (Alopex lagopus) dans la vallée de la Karupelv (Groenland oriental). Malgré sa faible densité, le lemming était la proie la plus courante, constituant 65,3 p. cent de poids fécal sec dans les excréments frais. Ce fait illustre l'importance de l'espèce du lemming comme proie pour le renard arctique durant un cycle complet de lemmings. Les oiseaux, le lièvre arctique (Lepus arcticus) et les insectes entraient aussi dans le régime alimentaire. Des restes de renard arctique donnent à penser que les renards se nourrissaient des charognes de leurs congénères. On a trouvé de petites quantités de plantes, de boeuf musqué (Ovibos moschatus) et de phoque (Phocidae). On a comparé les estimations de la disponibilité des proies et le régime des renards arctiques pour ...